Cancer patients' perceptions of quality-of-care attributes—Associations with age, perceived health status, gender and education - Suhonen, Riitta A.; Stolt, Minna; Berg, Agneta C.; Katajisto, Jouko; Lemonidou, Chryssoula; Patiraki, Elisabeth; Sjövall, Katarina; Charalambous, Andreas (My University, 2018)
Aims and objectives: The aim of this study was to explore the associations between patients' gender, education, health status in relation to assessments of patient-centred quality and individuality in care and trust in nurses for those <65 (working age) and ≥65 years (older people). Background: Patients' assessments of the quality of care they receive are essential for the development of the provision of patient care and services. Previous studies have revealed age of the patient is associated with their assessment of care quality attributes. Design: The study employed a cross-sectional, multicultural comparative survey design. Methods: The data were collected using questionnaires among hospitalised cancer patients (N = 876, n = 599, 68%) in four European countries: Greece, Cyprus, Sweden and Finland. The data were divided into two subgroups based on age (cut point 65 years) and were analysed statistically. Results: Cancer patients' age, gender and level of education were not related to their assessments of care quality attributes: person-centred care quality, individuality in care and trust in nurses. Subgroup analysis of the older adults and those of working age showed clear associations with patients' assessments of quality-of-care attributes and perceived health status. The lower the perceived health status, the lower the assessment of care quality attributes. Discussion: The results suggest that the cancer itself is the strongest determinant of the care delivered, rather than any patient characteristics, such as age, education or gender. Perceived health status, in association with cancer patient assessments of care quality attributes, may be useful in the development of patient-centred, individualised care strategies alongside a stronger focus on people instead of cancer-care-related processes and duties. Conclusions: Health status was the only factor associated with cancer patients' assessments of care quality attributes. Cancer itself may be the strongest determinant of the care quality perceptions, rather than any patient characteristics. Relevance to clinical practice: The findings of this study have implications for cancer care professionals in terms of patient assessment and care planning. The measures may be useful in assessing quality of cancer nursing care.
Keywords: Age; Cancer; Education; Gender; Health status; International; Patient; Person-centred care; Quality; Survey